2020
DOI: 10.4103/joc.joc_120_19
|View full text |Cite
|
Sign up to set email alerts
|

The genotoxic and cytotoxic effects of CT scan on buccal epithelial cells

Abstract: Background: Diagnostic radiation is reported to cause significant damage in buccal cells, while the same effects after natural cell turn over cycle were not checked for in previous studies. The buccal cells were studied in patients exposed to computed tomography (CT) scans for evaluating the cells with micronuclei and cytotoxic changes, namely, pyknotic cells, karyorrhectic cells and karyolytic cells. The pre-exposure counts were compared with postexposure counts on 10 and 20 days corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They collected the buccal mucosal cell samples 10 and 20 days after exposure and evaluated them by using light microscopy. 29 They concluded that genotoxicity significantly increased after 20 days; however, the level of cytotoxicity observed after 10 days significantly decreased in the second cell cycle at 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…They collected the buccal mucosal cell samples 10 and 20 days after exposure and evaluated them by using light microscopy. 29 They concluded that genotoxicity significantly increased after 20 days; however, the level of cytotoxicity observed after 10 days significantly decreased in the second cell cycle at 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…It may be correlated with dosedependent radiation damage. A study compared cytotoxic changes in buccal cells post-exposure to CT scans showed that the cytotoxic changes have significantly decreased after 20 days or second cell turnover (16). It means that a CT scan induced temporary damage to the cell.…”
Section: Discussionmentioning
confidence: 99%
“…It means that a CT scan induced temporary damage to the cell. The CBCT has 10-12 times less dose than CT scan, and panoramic radiography had a lower dose than CBCT (16). Therefore, it may be assumed that cytotoxic effects from panoramic and CBCT on the gingiva and buccal mucosa do not persist for a prolonged period.…”
Section: Discussionmentioning
confidence: 99%
“…Cells require three to six genetic mutations to become carcinogenic, and these accumulate over time [14]. In humans, buccal epithelial cells turn over 7-10 days [15]. Most epithelial cells have a short lifespan and cannot accumulate the genetic mutations necessary for oral squamous cell carcinoma (OSCC) to develop [16,17].…”
Section: Carcinogenesis Can Be Explained By Cscs and Pcscsmentioning
confidence: 99%